2018
DOI: 10.1186/s12886-018-0914-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of anti-VEGF therapy in retinitis pigmentosa: a case report

Abstract: BackgroundRetinitis pigmentosa (RP), a neurodegenerative disease, is occasionally accompanied by choroidal neovascularization (CNV) and cystoid macular oedema. It is presently treated with repeated intravitreal injections of anti-vascular endothelial growth factor (VEGF) agents. However, there are concerns regarding long-term inhibition of VEGF by the use of these agents, especially in cases involving neurodegenerative diseases, since VEGFs have a neuroprotective effect. Currently, there are no reports on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…For several years, this information could only be attained through case reports [9,20,21]. In our study, a CNVM was observed in only one eye from one female patient (prevalence: approximately 0.09%).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For several years, this information could only be attained through case reports [9,20,21]. In our study, a CNVM was observed in only one eye from one female patient (prevalence: approximately 0.09%).…”
Section: Discussionmentioning
confidence: 74%
“…Epiretinal membranes (ERMs) and cystoid macular oedema (CME) are the most common macular abnormalities in RP patients, as detected by optical coherence tomography (OCT). Other macular abnormalities also accompanied by, such as macular holes (MH), vitreomacular traction syndrome (VMT) and choroid neovascularisation membrane (CNVM) [5][6][7][8][9]. To the authors' knowledge, visual acuity and prevalence of ocular abnormalities, have not yet been reported in a large cohort of Western Chinese RP patients.…”
Section: Introductionmentioning
confidence: 98%
“…CNVM are rare, and until recently, no data have shown the prevalence of CNVMs in RP patients. For several years, this information could only be attained through case reports [9,14,25]. In our study, a CNVM was observed in only one eye from one female patient (prevalence: approximately 0.09%).…”
Section: Discussionmentioning
confidence: 74%
“…CNVM was de ned as cystic macular edema associated with a disruption of the Bruch membrane/retinal pigment epithelium complex, accompanied by an avascular structure emanating from the deep capillary plexus appearing as a hyper-re ective lesion connected with the subretinal pigment epithelium. And other diseases that cause macular CNV were excluded [9,14].…”
Section: Age Of Onset and Functional Examinationmentioning
confidence: 99%
See 1 more Smart Citation